Performance measurement in retailing organisations using DEA - Vaz, Clara B. (2004)
This study describes an application of DEA to the assessment of operational and commercial efficiency of grocery stores from a major retailer. The operational perspective assesses the sales and income generated at the store. The commercial perspective assesses the sales of individual sections within the store. The effect of environmental variables on store performance, such as the population and the number of competitors in the surrounding area, is also analysed. These models are refined with the inclusion of weight restrictions to reflect accurately the relative importance of the input and output variables on the store performance.